An Experimental Study on Friction Stir Processing of AA-7020 Aluminum Alloy - Ilkhechi, Atabak Rahimzadeh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: Friction stir processing (FSP) as a promising thermo mechanical approach aims on altering the microstructural and mechanical properties of material in order to obtain the highest performance (increasing or decreasing of hardness and tensile) in terms of properties, cost and lead time. This study addresses FSP of AA-7020 aluminum alloy. The effect of variation in the ratio of rotational and translational speeds (i.e., ω/f) is examined on the mechanical properties and microstructure of AA-7020 aluminum alloy. The value of ω/f (ω is rotational speed f is feed rate) is varied from 22 rev/mm to 125 rev/mm. The results show that with increasing ω/f, the grain size decreases. When ω/f (ω is rotational speed f is feed rate) ranges from 22 to 28, average hardness, ultimate strength and yield strength increase from 75 HV to 103 HV, from 313 to 364 MPa and from 173 MPa to 208 MPa, respectively. However, for ω/f ranging from 28 to 125, a reduction has been noticed in these properties. Regarding microstructure, it is found that the size of grain in the processed zone is small and the direction of grain is random. Besides mechanical properties, observations regarding the effect of ω/f on surface quality are also made to show that larger values of ω/f lead to poor surface texture. Keywords: Friction Stir Processing, Hardness, Impact, Quality, Microstructure, Tensile, AA-7020. ………………………………………………………………………………………………………………………… ÖZ:Sürtünme hareketlenme işlemi (FSP) termo mekanik işleme tekniklerini kullanarak malzemelerin mikroyapı ve mekanik özelliklerini değiştiriyor ki bu üretim masraflarını ve zamanı azaltıyor ve yüksek performans elde etmeğe neden oluyor. Bu çalışmada, Sürtünme hareketlenme işlemi (FSP) soğuk çekilen AA-7020 alaşımı üzerınde kullanılmıştır . Dönme ve öteleme hızı oranı (ω/f), 22 ve 125 (devir/mm) arasında değişmiştir. Adı geçen parameternin mikroyapı ve mekanik özellikler etkilamasi incelenmiştir.Sonuçlarına göre, FSP tanelerin boyunu operasıyon bölgesınde azaltmştır.Nezaman ω/f artmışsa tanelerin boyu azaltmştır. Beli bir aralık için, 0 ile 22 arasında ortalama sertlik artmıştır ve 0 ile 22 aralık için arasında gerilme mukavemeti artmaktadır ki bunlar soğuk çekilen malzemelerin darbe dayanımı ve yumuşaklık azalmasına neden oluyorlar.Halbuki, daha sonra ortalama sertliği 28 ve 125 oranlar arasında ve gerilme mukavemeti 28 ve 125 oranlar arasında ters oluyor.Yukarıdaki parametrenin etkisi yüzey kalitesi nin üzerine görsel olarak gözlenmiştir. Bulunmuştur ki yüzey kalitesi,, ω/f artmasıyla iyileşmektedir. Mikro sonuclarına göre operasıyon bölgesınde tanelerin boyu küçük ve onların yönleri belirsizdir. Beli bir aralık için, 0 ile 22 arasında malzemelerin darbe dayanımı artmıştır Halbuki, daha sonra tekrar azalmıştır. Anahtar Kelimeler: Sürtünme hareketlenme işlemi,Mikroyapı, Sertlik, Çekme Darbe, Kalite,AA-7020.
Master of Science in Mechanical Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2014. Supervisor: Assist. Prof. Dr. Ghulam Hussain.
Keywords: Mechanical Engineering; Friction welding; Friction Stir Processing, Hardness, Impact, Quality, Microstructure, Tensile, AA-7020